Intermixing of metal oxide/Ag/metal oxide nanoscale multilayers prepared by rf reactive magnetron sputtering - Hasan, M.M.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan (Maney Publishing, 2011)
This study mainly aims to evaluate the intermixing between layers during the deposition of dielectric/metal/dielectric nanoscale multilayer coatings. TiO(2) and WO(3) films as dielectric materials are developed using radio frequency reactive magnetron sputtering on unheated soda lime glass substrates. Ag films are grown using radio frequency argon sputtering. Auger electron spectroscopy and ultraviolet-visible-near infrared spectrometry are employed to estimate the degree of layer intermixing in TiO(2)/Ag, WO(3)/Ag, TiO(2)/Ag/TiO(2) and WO(3)/Ag/WO(3) films. The morphological properties are also investigated under a field emission scanning electron microscope and an atomic force microscope. The transmittance curves for bilayer films exhibited heat mirror effects significantly. However, multilayer films showed a little amount of heat mirror effects. Auger electron spectroscopy depth profiles confirmed a minor diffusion of Ag at the TiO(2)/Ag interface. However, significant interactions of WO(3) with Ag were observed for the WO(3)/Ag film. Besides, severe intermixing and oxidation of Ag films were observed for the multilayer films.